2007
DOI: 10.1186/1472-6750-7-70
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating B lymphocytes as an efficient source of highly specific immunoglobulins recognizing tumor cells

Abstract: Background: There is much evidence that tumor cells elicit a humoral immune response in patients. In most cases, the presence of antibodies in peripheral blood is detected only in small proportion of patients with tumors overexpressing the corresponding antigen. In the present study, we analyzed the significance of local humoral response provided by tumor-infiltrating lymphocytes in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 41 publications
6
36
0
Order By: Relevance
“…In future, we will examine whether such autoantibodies exist in the sera of HCC patients. Pavoni et al showed that breast tumor tissues containing B cells are an efficient source for constructing phage display libraries [20]. Based on their results, we constructed a library derived from HCC patient tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future, we will examine whether such autoantibodies exist in the sera of HCC patients. Pavoni et al showed that breast tumor tissues containing B cells are an efficient source for constructing phage display libraries [20]. Based on their results, we constructed a library derived from HCC patient tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Reasonably, the phage library derived from B cells of tumor patients can provide antibody fragments against specific tumor antigens. Pavoni et al reported that high-affinity phage clones against tumor antigens are isolated using a library derived from the peripheral blood cells of breast tumor patients [20]. In this study, we attempted to produce a human scFv specific for Lu using phage libraries displaying scFv derived from HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although most previous studies have used non-fixed living cells as the targets to screen for cancer cell antibodies (7,19,20), some researchers still prefer to use PFA fixed cells to screen for antibodies. Fixed cells ensure the integrity of the cell membrane during the entire process (21,22), decrease cell breakage and antigen degradation and avoid the inhibition of bacterial growth caused by hydrolytic enzymes and other harmful substances released by the breakdown of residual cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pathology of breast cancer has been shown to be associated with alterations of different components of body's immune machinery (78)(79)(80)(81). It has been recently proposed that inflammation, in part due to tumor-associated macrophages and proinflammatory cytokines, may promote more aggressive ER-positive tumors and the suggested treatment includes targeting inflammation combined with anti-estrogenic drugs (82).…”
Section: Discussionmentioning
confidence: 99%